Adhesion of Leukocytes to Cerebral Venules Precedes Neuronal Cell Death and Is Sufficient to Trigger Tissue Damage After Cerebral Ischemia - Sienel, Rebecca Isabella; Kataoka, Hiroharu; Kim, Seong-Woong; Seker, Fatma Burcu; Plesnila, Nikolaus (Frontiers in Neurology, 2022)
Background: Leukocytes contribute to tissue damage after cerebral ischemia, however, the mechanisms underlying this process are still unclear. The aim of the current study was to investigate the temporal and spatial relationship between vascular leukocyte recruitment and tissue damage and to uncover which step of the leukocyte recruitment cascade is involved in ischemic brain injury. Methods: Male wild-type, ICAM-1 deficient, anti-CD18 antibody treated, or selectin deficient (FucT4/7-/-) mice were subjected to 60 minutes of middle cerebral artery occlusion (MCAo). The interaction between leukocytes and the cerebro-vascular endothelium was quantified by in vivo fluorescence microscopy up to 15 hours thereafter. Temporal dynamics of neuronal cell death and leukocyte migration were assessed at the same time points and in the same tissue volume by histology. Results: In wild-type mice, leukocytes started to firmly adhere to the wall of pial post-capillary venules two hours after reperfusion. Three hours later, neuronal loss started and 13 hours later leukocytes transmigrated into brain tissue. Loss of selectin function did not influence this process. Application of an anti-CD18 antibody or genetic deletion of ICAM-1, however, significantly reduced tight adhesion of leukocytes to the cerebro-vascular endothelium (-60%; P<0.01) and increased the number of viable neurons in the ischemic penumbra by 5-fold (P<0.01); the number of intraparenchymal leukocytes was not affected. Conclusions: Our findings suggest that ischemia triggers only a transient adhesion of leukocytes to the venous endothelium and that inhibition of this process is sufficient to partly prevent ischemic tissue damage.